2016
DOI: 10.2174/2211550105666160322234434
|View full text |Cite
|
Sign up to set email alerts
|

The Search for a Lipid Trigger: The Effect of Salt Stress on the Lipid Profile of the Model Microalgal Species Chlamydomonas reinhardtii for Biofuels Production

Abstract: Background: Algal cells produce neutral lipid when stressed and this can be used to generate biodiesel.Objective: Salt stressed cells of the model microalgal species Chlamydomonas reinhardtii were tested for their suitability to produce lipid for biodiesel.Methods: The starchless mutant of C. reinhardtii (CC-4325) was subjected to salt stress (0.1, 0.2 and 0.3 M NaCl) and transesterification and GC analysis were used to determine fatty acid methyl ester (FAME) content and profile.Results: Fatty acid profile wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…At this point, the cells that were not adapted to environmental stress showed a severely damaged, clustered appearance (Fig. 3 B-1), similar to what was observed in Chlamydomonas reinhardtii [ 21 ]. Moreover, strong green fluorescence indicated that the cells had suffered severe oxidative damage (Fig.…”
Section: Resultssupporting
confidence: 73%
“…At this point, the cells that were not adapted to environmental stress showed a severely damaged, clustered appearance (Fig. 3 B-1), similar to what was observed in Chlamydomonas reinhardtii [ 21 ]. Moreover, strong green fluorescence indicated that the cells had suffered severe oxidative damage (Fig.…”
Section: Resultssupporting
confidence: 73%
“…Neutral lipids may have played a vital role in controlling the development of major structures in plants 52 . Numerous species of single-celled microalgae can store bulky volumes of TAG under nutrient and salt stress circumstances 53 , 54 . The salt tolerant green alga Dunaliella salina (Teodoresco) is unique in that it stores, under high irradiances or nitrogen deficiency, huge quantities of plastidic lipid droplets, which are composed of TAG and two isomers of beta-carotene 55 .…”
Section: Discussionmentioning
confidence: 99%
“…The lipid production from green microalgae species generally possess a fatty acid profile containing predominantly C16 and C18 fatty acids, similar to that of vegetable oils and therefore fit for biodiesel production 56 . In general, greater salinity has a valuable effect on microalga metabolite (such as lipid) production 40 , 54 . According to the results achieved in the present study, maximum cell growth, biomass concentration (1231.66 ± 1.26 mg L −1 ), and lipid content (248.33 mg L −1 ) were found at 2 M NaCl, while the lipid content per biomass percentage (22.28%) was observed at the 2.5 M NaCl levels.…”
Section: Discussionmentioning
confidence: 99%
“…Increased neutral lipid or TAG content along with increased salinity also occurs in several species such as Tetraselmis suecica [11] and Scenedesmus sp. [14]. Based on the results of observations during culture (Figure 4), the daily temperature ranges from 29-30 o C. There is no significant temperature change as long as the culture takes.…”
Section: Lipid Content Chaetoceros Muellerimentioning
confidence: 96%